2013
DOI: 10.15517/rbt.v61i3.11972
|View full text |Cite
|
Sign up to set email alerts
|

Efectos toxicológicos del uso prolongado e intenso de emisiones de espirales contra mosquitos en ratas y sus implicaciones sobre el control de la malaria

Abstract: Efectos toxicológicos del uso prolongado e intenso de emisiones de espirales contra mosquitos en ratas y sus implicaciones sobre el control de la malaria. Mosquito coil is a vector control option used to prevent malaria in low income counties, while some studies have addressed this issue, additional reseach is required to increase knowledge on the adverse health effects caused by the prolonged use of coils. In this study we investigated the toxicological effects of fumes from two locally manufactured mosquito … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Moreover, obtained data also showed signi cant increase in serum EPO hormone in both exposed groups. Idowu et al (2013) suggested that the increase in EPO hormone is responsible for stimulating bone marrow to produce RBCs to overcome hypoxia. In turn, the maintenance of normal levels of hematological parameters in the present study can be attributed to the increase of EPO hormone in the exposed groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, obtained data also showed signi cant increase in serum EPO hormone in both exposed groups. Idowu et al (2013) suggested that the increase in EPO hormone is responsible for stimulating bone marrow to produce RBCs to overcome hypoxia. In turn, the maintenance of normal levels of hematological parameters in the present study can be attributed to the increase of EPO hormone in the exposed groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, obtained data also showed significant increase in serum EPO hormone in both exposed groups. Idowu et al ( 2013 ) suggested that the increase in EPO hormone is responsible for stimulating bone marrow to produce RBCs to overcome hypoxia. In turn, the maintenance of normal levels of hematological parameters in the present study can be attributed to the increase of EPO hormone in the exposed groups.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the use of pyrethrin-based mosquito coils can significantly increase the number of leukocytes, particularly basophils and lymphocytes (Garba et al, 2007;Al-Mamun et al, 2017). Long-term exposure to pyrethroids can also affect the biochemical parameters of blood (Narendra et al, 2007;Idowu et al, 2013), increase the levels of reactive oxygen species (ROS), and lead to over-expression of the gene p53, which is considered the first stage of cellular apoptosis mediated by mitochondria (Madhubabu & Yenugu, 2012).…”
mentioning
confidence: 99%